The Fur Bringers: A Story of the Canadian Northwest - Footner, Hulbert, 1879-1944 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Fur Bringers: A Story of the Canadian Northwest" by Hulbert Footner is a historical novel written in the early 20th century. Set against the backdrop of the Canadian fur trade, the story revolves around Ambrose Doane, a young free trader, and his interactions with his partners and the local community, including the trader's spirited daughter, Colina Gaviller. The narrative explores themes of rivalry, romance, and the complexities of life in a frontier setting. The opening of the novel introduces us to Ambrose Doane and his partner, Peter Minot, who run a trading post on Lake Miwasa. Tension brews between the two partners, revealing a backdrop of camaraderie and conflict in their work life, compounded by Ambrose's feelings of restlessness and emotional turmoil, described as "June fever." As the story unfolds, we learn about Colina Gaviller, a strong-minded and adventurous woman, who captures Ambrose's fascination. Their first encounter is charged with tension and attraction, setting the stage for a deeper exploration of their relationship amidst the challenges posed by their environment and societal expectations. The initial chapters establish the emotional stakes and the characters' backgrounds, offering a rich setting for Ambrose's impending journey and the dynamics of frontier life. (This is an automatically generated summary.)
Release date is 2005-07-13
Produced by Al Haines
Keywords: Northwest, Canadian -- Fiction